Jawabanmu

2014-08-21T23:29:23+07:00
2x - y + z = 3  .... (i)
x + 3y - 2z = 11 .... (ii)
3x - 2y + 4z = 1 .... (iii)

(i) 2x - y + z = 3        x 1  -->  2x - y + z = 3
(ii) x + 3y - 2z = 11   x 2  -->  2x + 6y - 4z = 22  _
                                                - 5y + 5z = -19  ... (iv)

(i) 2x - y + z = 3        x 3  -->  6x - 3y + 3z = 9
(iii) 3x - 2y + 4z = 1  x 2  -->  6x - 4y + 8z = 2  _
                                                    y - 5z = 7 .... (v)

(iv) -5y + 5z = -19  x 1    -5y + 5z = -19
(v) y - 5z = 7          x -5   -5y + 25z = -35  _
                                               -20z = 54
                                                   z = 2,7

(iv) -5y + 5z = -19  x 1    -5y + 5z = -19
(v) y - 5z = 7          x -1     -y + 5z = -7    _
                                         - 4y = - 12
                                             y = 3

(i) 2x - y + z = 3
⇔ 2x - 3 + 2,7 = 3
⇔ 2x - 0,3 = 3
⇔ 2x = 3,3
x = 1,65

maka nilai x, y, z = 1,65 , 3 , 2,7
5 4 5